The retina as a window to the basal ganglia: Systematic review of the potential link between retinopathy and hyperkinetic disorders in diabetes. (November 2020) - Lizarraga, Karlo J.; Chunga, Natalia; Yannuzzi, Nicolas A.; Flynn, Harry W.; Singer, Carlos; Lang, Anthony E.
Abstract: There is evidence that glycemic fluctuations trigger vascular-mediated dysfunction in both the retina and the striatopallidal regions in patients with diabetes. The latter is associated with a variety of hyperkinetic disorders that are rare but disabling and potentially preventable. We conducted a systematic review of the potential association between diabetic retinopathy and the risk and prognosis of hyperkinetic disorders in patients with diabetes. We identified a total of 461 articles and 147 were eligible for review. Nine out of 147 articles (6.12%) reported 13 patients with information on diabetic retinopathy. Glycemic fluctuations were present at onset in 10 patients (77%) and retinopathy was present in nine of them (69.23%). The degree of retinopathy was reported in four patients. Two had severe, bilateral proliferative retinopathy, one had moderate-to-severe non-proliferative retinopathy and one had non-proliferative retinopathy. In the nine patients with retinopathy, hyperkinesia persisted, required higher doses of dopamine receptor antagonists or deep brain stimulation. Retinopathy was absent in four cases (30.77%). In these patients, hyperkinesia resolved spontaneously or with lower doses of dopamine receptor antagonists. Diabetic retinopathy could be an indirect marker of striatopallidal microangiopathy in patients with diabetes. The severity of retinopathy may be associated with increased risk or worse prognosis for patients who develop hyperkinetic disorders of the diabetic striatopathy spectrum. Early detection of retinopathy could identify patients in which avoiding glycemic fluctuations may prevent the development of striatopathy and hyperkinetic disorders. Highlights: In diabetes, vascular dysfunction occurs in the retina and striatopallidal regions. Glycemic fluctuations often precede deterioration in retinopathy and striatopathy. Diabetic retinopathy could be an indirect marker of striatopallidal microangiopathy.